2016
DOI: 10.1080/13545701.2016.1181272
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Deportation and Rescue: Economies of Migration among Nigerian Sex Workers

Abstract: This contribution explores the economies interlinked by the migration of Nigerian women sex workers. The literature and politics of sex work migration and human trafficking economies are commonly relegated to the realm that focuses on profits for criminal networks and pimps, in particular recirculating the claim that human trafficking is the "third largest" criminal economy after drugs and weapons. Based on ethnographic fieldwork among Nigerian sex worker migrants conducted in Benin City, Nigeria, in 2011 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…This contribution has shown that agency is an empirical and conceptual lynchpin of the collection of studies in this issue. Agency comes through and varies with subjective as well as objective bargaining power (Hui 2017); legalization, as currently enforced, need not imply full agency (Verhoeven and van Gestel 2016); failing to see agency (however limited) leads to mistaking indentured forms of sex work migration for trafficking (Plambech 2016); agency comes as choice of the type of sex work (Mathews 2017); agency is implied by any economic choice, but is always constrained (Botti and D'Ippoliti 2016;Della Giusta, Di Tommaso, and Jewell 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This contribution has shown that agency is an empirical and conceptual lynchpin of the collection of studies in this issue. Agency comes through and varies with subjective as well as objective bargaining power (Hui 2017); legalization, as currently enforced, need not imply full agency (Verhoeven and van Gestel 2016); failing to see agency (however limited) leads to mistaking indentured forms of sex work migration for trafficking (Plambech 2016); agency comes as choice of the type of sex work (Mathews 2017); agency is implied by any economic choice, but is always constrained (Botti and D'Ippoliti 2016;Della Giusta, Di Tommaso, and Jewell 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Hui (2017), in this volume, is interested in how stigma matters on the supply side: in her framework stigma influences bargaining power, rather than separating markets, and one of her key findings is that perceived bargaining power is affected by stigma more than actual bargaining power, thus providing a more explicit understanding of the link between stigma and agency. In the same vein, Plambech (2016) illustrates how, for Nigerian women involved in the trafficking flows of sex workers to Europe, being deported back to Benin city from Europe carries higher stigma than having been (trafficked as) sex workers. The reason, Plambech argues, is that deportation is equated with downward social mobility since, after deportation, former migrants can no longer support their family with their remittances.…”
Section: Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…That anti-trafficking efforts control the very people they aim to protect reveals the punitive dimensions of carcerally oriented anti-trafficking efforts (Musto 2016(Musto , 2019. Consider: migrant women deemed "at risk" of trafficking continue to face deportation and heightened state surveillance (Doezema 2002;O'Connell Davidson 2006;Plambech 2017). Meanwhile, LGBT sex workers, though recognized as particularly vulnerable to trafficking (Department of State 2014), are rarely legible to authorities as victims (Boukli and Renz 2019) nor offered supportive services and legal protection.…”
Section: Sexual Humanitarianism and Anti-traffickingmentioning
confidence: 99%
“…When Ioana and Dragos finally manage to repay their debt following a long working year in the streets of Copenhagen, they arrive home without money and have to take up a new loan with another cămătar to cover for expenses at home during the winter period. In this sense, the debt is not caused by the migration process as has been illustrated in research on some migrants from Nigeria (Plambech 2017). Rather, debt appears as an integral component of the badocari household economy prior to the migration process, and in fact encourages mobility (to earn money for repayment) as well at it is perpetuated by the migration process (when taking up new loans to pay for travel costs).…”
Section: Patchwork Household Economies Configured Around Debtmentioning
confidence: 95%